Livestock development and climate change: The benefits of advanced greenhouse gas inventories - Global Research Alliance on Agricultural Greenhouse Gases; CGIAR Research Program on Climate Change, Agriculture and Food Security (Global Research Alliance on Agricultural Greenhouse Gases, 2016)
Livestock development and climate change outcomes can support each other. More productive and e cient farm systems generally produce food at much lower greenhouse gas (GHG) emissions per unit of product.